2019
DOI: 10.3892/or.2019.7048
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of microRNA expression profiles reveals a 5‑microRNA prognostic signature for predicting overall survival time in patients with gastric adenocarcinoma

Abstract: There is growing evidence supporting dysregulated microRNAs (miRNAs) as potential prognostic biomarkers in cancer. The present study aimed to identify an miRNA model set with prognostic power for patients with gastric adenocarcinoma. miRNA-seq data from 155 patients and 37 controls were downloaded from The Cancer Genome Atlas (TCGA) database for a comprehensive analysis of miRNA expression profiles and were used as training data. A total of 5 prognostic miRNAs, which have not been previously reported, were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…An appropriate formula was developed to use this panel. However, the authors have shown that a history of relapse and age over 65 years are independent prognostic factors [146].…”
Section: Mir-585mentioning
confidence: 99%
“…An appropriate formula was developed to use this panel. However, the authors have shown that a history of relapse and age over 65 years are independent prognostic factors [146].…”
Section: Mir-585mentioning
confidence: 99%
“…Gene regulation is a complex network, and researchers began to use sequencing data to build a multi-gene model, combined with multiple gene detection to study tumors. For example, Zhao et al (2019) used univariate and multivariate Cox regression analysis to identify miRNA related to GC patients’ prognosis from the TCGA-STAD cohort. A predictive risk model based on a 5-miRNA signature was established.…”
Section: Introductionmentioning
confidence: 99%